Impaired long-term anti-HBs responses in choronic hepatitis C patients: Results from a five-year follow-up study with healthy control - Bingyu Yan; Jingjing Lu; Liqiu Jia; Yi Feng; Jing Wang; Xin Meng; Xiaofeng Liang; Fuzhen Wang; Yanmin Wan; Aiqiang Xu; Li Zhang (Taylor & Francis Group, 2023)
Although hepatitis B virus (HBV) vaccination is recommended for hepatitis C virus (HCV)-infected individuals to avoid HBV superinfection, the persistence of their humoral and cell-mediated immunity responses to HBV vaccination is still under investigation. Patients with chronic hepatitis C (CHC) and matched healthy controls, who completed three doses of hepatitis B vaccine (HepB) in 2014, were followed up five years later. One booster dose of HepB was given to those with antibody against hepatitis B surface antigen (anti-HBs) lower than 10mIU/mL. Anti-HBs was tested at follow-up and on the 14th day after the booster dose, as well as HBsAg specific spot-forming cells of interferon γ and interleukin (IL) 2, 4, 5, and 6. At five years, only 56.58% of the CHC patients had sero-protective titers (≥10mIU/mL) of anti-HBs, compared to 70.83% in the controls (P < .05). Similarly, the geometric mean concentration (GMC) of anti-HBs in CHC patients was significantly lower than that in controls (16.95 vs 37.34 mIU/mL, P < .05). After the booster, both GMC and the rate of anamnestic response increased to a very high level in the two groups and the difference between them disappeared (P > .05). Multivariable analysis showed that HCV infection was an independent predictor factor to anti-HBs level at follow-up. HBsAg specific IL-6 was stronger in the CHC patients compared to the controls (P < .05). The data indicate that the durability of protective anti-HBs is poorer in CHC patients compared to healthy individuals, and impaired long-term anti-HBs responses might be associated with the increased HBsAg specific IL-6 responses.